Pancasila Values as Strengthening Character Building during the Covid -19 Pandemic - S, Leo Agung (Universitas Sebelas Maret, 2021)
Pancasila values as the noble values of the Indonesian nation have existed since our ancestors. The divine precepts are related to animism and dynamism, which continued to develop during the Hindu Buddhist and Islamic kingdoms until now. During the Majapahit Empire, the religious values of Pancasila were strengthened by the existence of two Hindu-Buddhist kingdoms that lived peacefully side by side. The value of unity and oneness is explicitly written by Mpu Tantular in the Sotosoma Book, namely Bhinneka Tungal Ika. Furthermore, when Bung Karno on June 1 issued five principles as the basis for the state he would form, which was named Pancasila, and finally on August 18, 1945, Pancasila was established as the State Foundation. After this state is formed, it is necessary to have a character building so that every citizen has a sense of love for the nation and homeland. That is why it is necessary to develop character that is rooted in the values of Pancasila, namely religious values, compassion, self-control, cooperation, mutual respect / respect, responsibility, and persistence in handling Covid-19. Thus the values of Pancasila reinforce character building.